The copper, zinc superoxide dismutase gene of penicillium marneffei: Cloning, characterization, and differential expression during phase transition and macrophage infection - Sophit Thirach (2018)
Superoxide dismutase (SOD) is an enzyme that converts superoxide radicals into hydrogen peroxide and oxygen molecules. SOD has been shown to contribute to the virulence of many human-pathogenic fungi through its ability to neutralize toxic levels of reactive oxygen species generated by the host. SOD has also been speculated to be important in the pathogenesis of fungal infections, but the role of this enzyme has not been rigorously investigated. In this report, we isolated and characterized the copper, zinc superoxide dismutase gene, designated sodA, from the important human pathogenic fungus, Penicillium marneffei. The putative SodA polypeptide consisted of 154 amino acids and exhibited a significant level of similarity to other fungal Cu, Zn SODs. Differential expression of the sodA gene in P. marneffei was demonstrated by semi-quantitative RT-PCR. Apparently, the sodA transcript accumulated in conidia, but expression was downregulated in the mycelia phase. In contrast, transcript expression was upregulated in the yeast phase as well as during macrophage infection. The significantly higher expression of the sodA transcript during macrophage infection suggests that this gene might play an important role in stress responses and in the adaptation of P. marneffei to the internal macrophage environment. The latter may serve as a putative virulence factor of this fungus allowing for survival in the host cell.